Under Pressure? Assessing the Roles of Skills and Other Personal Resources for Work-Life Strains - Niels-Hugo Blunch; David Ribar; Mark Western (Global Labor Organization (GLO), 2018)
Many working parents struggle to balance the demands of their jobs and family roles. Although we might expect that additional resources would ease work-family constraints, theory and evidence regarding resources have been equivocal. This study uses data on working mothers and fathers—as well as their cohabiting partners/spouses—from the Household, Income, and Labour Dynamics in Australia survey to investigate how personal resources in the form of skills, cognitive abilities, and personality traits affect work-life strains. It considers these along with standard measures of economic, social, and personal resources, and estimates seemingly unrelated regression (SUR) models of work-life strains for employed mothers and fathers that account for correlations of the couple's unobserved characteristics. The SUR estimates indicate that computer skills reduce work-life strains for mothers, that math skills reduce strains for fathers, and that the personality traits of extraversion, conscientiousness, and emotional stability reduce strains for both parents. However, the estimates also indicate that better performance on a symbol look-up task, which tests attention, visual scanning acuity, and motor speed, increases fathers' work-life strains.
Keywords: I1; I31; J24; J81; 330; Work-family strains and gains; cognitive abilities; skills; household resources; Australia; HILDA survey